ความเครียดของพยาบาลจบใหม่ที่ปฏิบัติงานในหอผู้ป่วยวิกฤต - เกื้อวงศ์, กฤดิญาดา; อ่วมตานี, อารีย์วรรณ (Journal of The Royal Thai Army Nurses, 2017)
การวิจัยนี้มีวัตถุประสงค์เพื่อบรรยายความเครียดของพยาบาลจบใหม่ที่ปฏิบัติงานในหอผู้ป่วยวิกฤต โดยใช้ระเบียบวิธีวิจัยเชิงคุณภาพแบบปรากฏการณ์วิทยาแบบตีความ คัดเลือกผู้ให้ข้อมูลแบบเฉพาะเจาะจง ได้แก่ พยาบาลวิชาชีพที่มีประสบการณ์การดูแลต่อเนื่องในหอผู้ป่วยวิกฤตน้อยกว่า 3 ปี จำนวน 14 คน เก็บรวบรวมข้อมูลโดยใช้การสัมภาษณ์แบบเจาะลึกร่วมกับการบันทึกเทป การสังเกตและการจดบันทึกภาคสนาม นำข้อมูลมาถอดเทปแบบคำต่อคำ และวิเคราะห์ข้อมูลตามวิธีการของ van Manen ผลการศึกษาความเครียดของพยาบาลจบใหม่ที่ปฏิบัติงานในหอผู้ป่วยวิกฤต มี 4 ประเด็น คือ 1) รู้สึกกดดันกับการทำงานของตนเอง 2) รู้สึกเครียดกับงานที่ได้รับมอบหมาย 3) ไม่มั่นใจว่าจะสื่อสารอย่างไรให้ทุกคนเข้าใจ และ 4) ร้องไห้เสียใจ คิดว่าผู้ป่วยจากไปเพราะตนเองดูแลไม่ดีจากการศึกษาครั้งนี้จะเห็นได้ว่า พยาบาลจบใหม่ต้องเผชิญกับเหตุการณ์ต่างๆ ทำให้เกิดความเครียด และยังไม่พร้อมที่จะปฏิบัติงานในหอผู้ป่วยวิกฤต เนื่องจากพยาบาลที่ดูแลผู้ป่วยวิกฤตต้องมีความรู้และทักษะในการวิเคราะห์และตัดสินใจแก้ไขปัญหาได้อย่างถูกต้อง รวดเร็วและช่วยเหลือผู้ป่วยได้ทันเหตุการณ์ ดังนั้นผู้บริหารการพยาบาลควรเตรียมความพร้อมสำหรับพยาบาลจบใหม่ให้ทราบถึงสภาพปัญหาและสถานการณ์จริงของชีวิตการทำงานในหอผู้ป่วยวิกฤตและในระยะแรกควรปฏิบัติงานภายใต้การดูแลของพยาบาลพี่เลี้ยง Stress of Newly Graduated Nurses Working at an Intensive Care Unit The purpose of this study was to describe stress of newly graduated nurses working at an Intensive Care Unit by using qualitative research based on Hermeneutic phenomenology. Purposive sampling was used to select 14 nurse entrepreneurs as informants who have been being the newly graduated nurses and worked in ICU less than 3 years were included and data were collected by using in-depth interviews with tape-recordings, observation, and field notes. Data were transcribed verbatim and analyzed by using content analysis van Manen’s method. The results display that there were 4 characteristics stress of newly graduated nurses working at Intensive Care Units : 1) Feeling pressure with their jobs 2) Feeling stress with their job assignment 3) Low confident to effectively communicate with tem and 4) Crying and guilty of patient’s death by thinking about careless . The study findings showed that the newly graduated nurses face with variant event causing stress and not ready to work at in ICU setting. Because nurses caring patient in ICU must have medical knowledge and skills in analyzing decision making to help their patients, accurately, rapidly, and timely, so nurse administrators should provide preparing the newly graduated nurses to know the condition of the problem, and the actual situation of working life in the ICU, in addition, the initial period of their work in the ICU should be under supervision of their mentors.